LENGTH-WEIGHT RELATIONSHIP OF Trichopodus pectoralis IN THE SPEECTRA (SPECIAL AREA FOR CONSERVATION AND FISH REFUGIA) OF PATRA TANI FLOODPLAIN, PALEMBANG - Haikal, Muhammad Faaris; Suryati, Ni Komang; Julian, David (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2024)
Floodplains are dynamic freshwater ecosystems characterized by significant ecological shifts between dry and rainy seasons. The snakeskin gourami (Trichopodus pectoralis), a resilient blackfish species, thrives in these extreme environments due to its specialized labyrinth breathing organ. However, its wild populations are declining, necessitating sustainable conservation strategies. This study evaluated the effectiveness of the special area for conservation and fish refugia (SPEECTRA) model, developed by BRPPUPP, in Patra Tani, Palembang. The SPEECTRA model leverages seasonal fish migration from rivers to floodplains during inundation, capturing fish in designated conservation ponds to facilitate spawning, protection, and production enhancement. Over a 30-day period at the Patra Tani Installation, purposive sampling was employed to collect T. pectoralis specimens. Growth patterns were analyzed using length-weight regression, and Fulton’s condition factor (Kn) was calculated. Results demonstrated that W=0.0108 L3.1076 with R2=0.9469. The growth pattern of the studied fish exhibited positive allometric characteristics, indicating that the population is likely in a favorable condition. This finding indicated the effectiveness of SPEECTRA as a fishery sanctuary, safeguarding key species such as T. pectoralis while mitigating anthropogenic pressures on aquatic ecosystems.Keywords: Aquatic organisms, sustainability, condition factor.